Code of ethics for Brazilian medical students. A literature review - Khouri, Jussara Mathias Netto; Bahia, Lilian; Rêgo, Francisca Melo Pojal da Silva; Nunes, Rui Manuel Lopes (Acta Bioethica, 2023)
In August 2018, the Federal Council of Medicine (CFM), the body responsible for the supervision and standardization of medical professional practice in Brazil, published a national code of ethics for medical students (CEMS), which standardizes and suggests behaviors, based on the best moral and ethical values, for medical students, supporting the humanization of medicine and indirectly helping teachers and managers of medical courses. The purpose of the study was to evaluate the dissemination and awareness of scientific publications on the Brazilian CEMS code and consisted of an integrative literature review of all publications related to the Brazilian CEMS published from 2005 to the present. We found 4 studies related to regional and university codes of ethics for medical students published from 2005 to 2022, and regarding the CEMS elaborated by the FCM, we found a single study from its launch in 2018 to 2022. A CEMS has universal importance, facilitating the ethical and human development of future physicians, and despite its importance in the training of physicians, there is a lack of published research on the subject in Brazil.